CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Solve the following equation:
$$(8x\, -\, 1)\, -\, (4x\, -\, \displaystyle \frac{1\, -\, x}{2})\, =\, 3x\, +\, \frac{1}{2}$$ 


A
2
loader
B
5
loader
C
3
loader
D
7
loader

Solution

The correct option is B $$2$$
$$(8x-1) - (4x-  \cfrac { 1-x }{ 2 } ) = 3x + \cfrac { 1 }{ 2 } \\ \\ \\2(8x-1) -(8x - 1 +x) = 6x +1\\ \\16x - 2 - 8x +1 -x = 6x +1\\\\ x = 2$$

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More



footer-image